Characterization and correction of multipole field effect on electron beams from a high-brightness continuous-wave photocathode gun - Haoyan Jia; Tianyi Li; Juntao Liu; Zhongqi Liu; Xiang Zhang; Jingyi Li; Kexin Liu; Cheng-Ying Tsai; Hang Xu; Senlin Huang (Physical Review Accelerators and Beams)
Continuous-wave photocathode guns are capable of delivering electron beams with high repetition rates and high average currents. However, they are limited by relatively low accelerating gradients and cathode fields. This limitation leads to a larger beam size at the gun exit due to space-charge forces, making the beam more sensitive to optical aberrations and posing challenges for low-emittance electron beam transmission. This paper focuses on the aberrations induced by multipole fields. We analyze the effects of quadrupole, sextupole, and higher-order fields on beam profile and transverse emittance and propose a beam-based method for the rapid characterization and correction of these multipole fields. Furthermore, we present an experimental study conducted on the DC-SRF-II photocathode gun equipped with dedicated correctors. Both simulation and experimental results demonstrate that our approach effectively mitigates beam aberrations caused by multipole fields, resulting in improved beam symmetry and reduced emittance.